Handbook of infectious disease data analysis - Held, Leonhard; Hens, Niel; O'Neill, Philip D.; Wallinga, Jacco (Boca Raton, FL : CRC Press, 2020)
Recent years have seen an explosion in new kinds of data on infectious diseases, including data on social contacts, whole genome sequences of pathogens, biomarkers for susceptibility to infection, serological panel data, and surveillance data. The Handbook of Infectious Disease Data Analysis provides an overview of many key statistical methods that have been developed in response to such new data streams and the associated ability to address key scientific and epidemiological questions. A unique feature of the Handbook is the wide range of topics covered. Key features Contributors include many leading researchers in the field Divided into four main sections: Basic concepts, Analysis of Outbreak Data, Analysis of Seroprevalence Data, Analysis of Surveillance Data Numerous case studies and examples throughout Provides both introductory material and key reference material
OCLC-licensed vendor bibliographic record.
Keywords: Communicable diseases -- Statistics; MEDICAL / Epidemiology; MEDICAL / Infectious Diseases